Methanol laser line assignments: evidence of four-level laser systems - Moraes, João Carlos Silos [UNESP]; Carelli, G.; Moretti, A.; Moruzzi, G.; Strumia, F. (My University, 1998)
The Ritz computer program, developed for facilitating the assignment of molecular Fourier transform absorption spectra and described in a previous work, determines the energy level values involved in the assigned transitions by the Rydberg-Ritz combination principle. Combining the data obtained from the analyses of high-resolution infrared (IR) and far-infrared (FIR) spectra, it is possible to predict possible FIR laser emissions of molecules. In the present work we have applied this method to the common isotopomer methanol, 12CH3 16OH, and obtained 14 proposed assignments for previously unassigned FIR laser lines. We also predict 15 possible new FIR laser emissions. For the first time, an assignment involving a four-level laser system with collisional population transfer to a slightly higher energy level is reported. © 1998 Academic Press.
Keywords: Absorption spectroscopy; Computer software; Infrared spectroscopy; Lasers; Light emission; Methanol; Molecules; Far infrared spectroscopy; Four level laser system; High resolution infrared spectroscopy; Methanol laser line assignment; Molecular Fourier transfer absorption spectra; Rydberg-Ritz combination principle; Molecular spectroscopy